Protein C and antithrombin III deficiency in an elderly patient presenting with pulmonary embolism - R. Khan; N. Mahiyuddin; R. Tasnim; M. M. Rishad; Q. T. Islam (Asian Journal of Internal Medicine)
Pulmonary embolism is a life-threatening condition, which if not detected and treated timely may lead to death. It is usually a consequence of deep vein thrombosis, which itself may occur due to several risk factors like prolonged immobilisation, surgery, long haul flights, obesity, previous or family history of thrombosis, intravenous drug abuse, oral contraceptive pills and conditions like antiphospholipid syndrome, paroxysmal nocturnal haemoglobinuria or myeloproliferative disorders. In the background of recurrent thrombosis since childhood, once the common causes are excluded, natural anticoagulant deficiencies like protein C, protein S or antithrombin III deficiency are considered. Here we present a case of a 72-year-old man with multiple comorbidities, presenting with cough, breathlessness and features suggestive of aspiration pneumonia. Despite treatment his condition worsened and further investigation revealed sub-massive pulmonary embolism due to protein C and antithrombin III deficiency, a rare occurrence in this age group. The patient did not have any other common risk factors for thrombosis. To the best of the authors’ knowledge this is the first reported case of such dual anticoagulant deficiency presenting only with pulmonary embolism in an elderly patient, which may have developed due to severe inflammatory state. However, after the initiation of anticoagulant therapy his condition gradually improved with resolution of symptoms and thrombus on follow-up imaging. This case highlights the importance of considering natural anticoagulant deficiency in elderly when common risk factors of clotting are excluded and also focuses on the diagnostic challenges along with therapeutic strategies employed in managing this case.